2021
DOI: 10.1186/s43094-021-00182-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemo-preventive efficacy of Ficus religiosa latex extract by flow cytometry analysis and gene expression studies performed by RT-PCR in various cell lines

Abstract: Background An extract of Ficus religiosa latex has been previously found to possess potent pharmacological activity with high antioxidant content phytochemical. The present research was conducted to investigate the chemo-preventive efficacy of latex extract on human breast adenocarcinoma MDA MB 231, human neroblastoma IMR 32, and human colorectal HCT 116 cell lines. Results The results showed that the latex crude extract induced cytotoxicity in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…At 500 μg/mL, very few cells appeared to have drastic changes, indicating high detachment and entering into the death phase, perhaps due to disturbance of the nuclear membrane. Other reports found similar effects, but using Calotropis procera latex [ 49 ] and Ficus religiosa latex extract [ 50 ]. The results of anticancer activity of latex were compared with adriamycin as positive control, with IC 50 , 58.07 μg/mL against PC3, and 38.20 μg/mL against MCF-7.…”
Section: Resultsmentioning
confidence: 56%
“…At 500 μg/mL, very few cells appeared to have drastic changes, indicating high detachment and entering into the death phase, perhaps due to disturbance of the nuclear membrane. Other reports found similar effects, but using Calotropis procera latex [ 49 ] and Ficus religiosa latex extract [ 50 ]. The results of anticancer activity of latex were compared with adriamycin as positive control, with IC 50 , 58.07 μg/mL against PC3, and 38.20 μg/mL against MCF-7.…”
Section: Resultsmentioning
confidence: 56%
“…Prominent morphological changes like loss of shape, disruption of the nuclear membrane and detachment of cells from the culture plate bottom were noticed, along with inhibition of cell growth and cell death after 24 h. Additional studies of apoptotic genes showed changes in their expression ( Table 3 ). Flow cytometry also showed cell arrest in the C1 and C2/M phase cancer cell lines treated with latex extracts ( Saida et al., 2021 ). F. religiosa , along with F. benghalensis , was also effective against MCF-7, leading up to 90% growth inhibition with 200 μg/ml concentration used ( Tulasi et al., 2018 ).…”
Section: Anticancer Properties Of Latex-bearing Plant Extractsmentioning
confidence: 99%
“…Cysteine proteinases (ficin) (Rubnov et al, 2001;Solomon et al, 2006;Hashemi et al, 2011) Ficus religiosa Flavonols (quercetin and myricetin) Phytosterols (stigmasterol and b-sitosterol) (Saida et al, 2021) Ficus pseudopalma 3) (Ghanbari et al, 2019). Fatma Mousa AlGhalban et al compared the activity of latex of F. carica and less studied Ficus specie F. salicifolia, native to the United Arab Emirates and used traditionally to treat cough, chest inflammation, scorpion stings and bruises (Gushash, 2006).…”
Section: Antiaris Toxicariamentioning
confidence: 99%
“…Unquestionably, recent research has demonstrated that latex contains numerous substances that are very useful in the fight against cancer. 30,31 Anticoagulant activity Researchers utilized PT time and powered incomplete thromboplastin time assays to assess the cell viability anticoagulation action of PT mucilage, and it was discovered that it possesses effective anticoagulant properties. [32][33][34][35] Antifungal activity T. peruviana seedlings were examined for antifungal photoactivity.…”
Section: Antibacterial Activitymentioning
confidence: 99%